Military iconography of Magna Graecia and Sicily Coinage Prior to Roman Expansion - Vico Belmonte, Ana (Eikón / Imago, 2022)
The aim of this study is to analyze the armorial coinage of Magna Graecia and Sicily (V-III BC) in order to find an interpretation of their iconography and message. The military theme is frequently repeated in ancient Greek numismatics; however, this research aims to locate the message launched and interpreted by ancient societies. To this end, the methodology followed has been to analyze the issues issued in these geographical areas before the Roman invasion and to compare the frequency of representations on each coin type and value in order to understand the reason of those themes’ selections according to the different coin values.